Developing technological capabilities in agro-industry: Ghana's experience with fresh pineapple exports in comparative perspective - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2010)
The time is ripe for an evidence-based discussion of what is 'private sector development' in Africa and how it occurs. This discussion requires analyses on how actual existing industries are created, expanded and remain competitive, and the role of industrial policy. This paper contributes to the discussion by examining the emergence and trajectory of a new agro-industry in Ghana: the pineapple export industry. It explores how this new agro-industry emerged as well as how it responded to changes in international competition. It explains the limited expansion of the industry and its declining international competitiveness by looking at how Ghanaian exporters developed technological capabilities initially and the incentives and disincentives to building those capabilities. The industry has its origins in Ghanaian professionals, civil servants and import businessmen who sought new economic opportunities in the 1980s and 1990s. The paper argues that at the heart of the industry's crisis was an inability to further develop technological capabilities. Both firm level and national level factors determine technological capability development. Thus, the crisis had systemic features that have broader implications for understanding the obstacles to developing new agro-industries in Ghana as well as other African countries. It also argues that small farmers can have a place in high-value agricultural export industries, but they must be linked into supply chains in ways that increase their capabilities. Where relevant, it compares Ghana's experience with that of the Ivory Coast and Costa Rica, its main competitors.
Keywords: 330